Theological Basis for Obedience to the Government During the Covid-2019 Pandemic in Indonesia - Supriadi, Made Nopen; Gulo, Manase; Halawa, Iman Kristina (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2021)
The Coronavirus Disease 2019 (Covid-19) pandemic continues to increase its spread. The government has made efforts to contain the space by enacting several health protocols by March 2020. However, many Indonesians have not followed through on this appeal, and this situation also occurs in the context of the church. The Covid-19 pandemic is predicted to subside at the end of August or early September 2020, but this has not been realized. The authors observe the phenomenon of failure to recognize this due to a lack of adherence to health protocols. Obedience is an important principle that needs to be understood and implemented by all Indonesian people, especially Christians and church leaders. This research used the descriptive method to identify the phenomenon to get to the main problem, namely the concept of obedience. This research got the theological formulation of obedience to the government, namely priestly service, political service, and submission to government policies that have justice and humanity values.Â Â ABSTRAKPandemi Coronavirus Disease 2019 (Covid-19) terus meningkat penyebarannya. Pemerintah telah melakukan upaya untuk mengatasi penyebaran dengan memberlakukan beberapa protokol kesehatan pada bulan Maret 2020, namun masih banyak masyarakat Indonesia belum menaati imbauan tersebut, dan situasi tersebut juga terjadi dalam konteks gereja. Pandemi Covid-19 diprediksi akan reda pada akhir Agustus atau awal September 2020, namun hal tersebut tidak terealisasi. Penulis mengamati fenomena gagalnya realisasi tersebut karena kurangnya ketaatan terhadap penerapan protokol kesehatan. Ketaatan adalah prinsip penting yang perlu dimengerti dan diimplementasikan oleh seluruh masyarakat Indonesia, secara khusus bagi umat Kristen dan para pemimpin gereja. Penelitian ini memakai metode deskriptif melakukan identifikasi fenomena untuk mendapatkan pokok permasalahan yaitu konsep ketaatan. Hasil penelitian menunjukkan formulasi teologis ketaatan kepada pemerintah yaitu pelayanan keimaman, pelayanan politis dan ketundukan kepada kebijakan pemerintah yang memiliki nilai keadilan serta kemanusiaan.